The Role of Career Guidance in Shaping Students’ Work Readiness: A Qualitative Phenomenological Study - Firayani, Firayani (Journal of Therapia, 2025)
The gap between formal educational attainment and labor market demands remains a persistent challenge in education systems, particularly during students’ transition from school to work. Career guidance is expected to support this transition; however, it is often implemented as an administrative activity rather than a developmental process that meaningfully prepares students for employment. This study aims to explore the role of career guidance in shaping students’ work readiness from the perspective of their lived experiences. Using a qualitative phenomenological design, this study involved in-depth semi-structured interviews with final-year senior high school and vocational school students who had participated in career guidance services. Data were analyzed through interpretative thematic analysis to capture patterns of meaning related to career preparation and readiness. The findings indicate that students perceive career guidance as effective when it facilitates self-understanding, clarifies career direction, and strengthens psychological readiness, including confidence and preparedness to face career transitions. Work readiness is experienced as a reflective and developmental process rather than the result of information transfer alone. The effectiveness of career guidance is strongly influenced by counselor competence, institutional support, program continuity, and contextual constraints within schools. This study concludes that career guidance plays a strategic role in developing students’ work readiness when implemented as a sustained, reflective, and contextually supported process. Integrating students’ experiential perspectives is essential for strengthening career guidance practices in educational settings.